2001
DOI: 10.1902/jop.2001.72.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and Inter‐Examiner Reproducibility in Keratinized Tissue Width Assessment With 3 Methods for Mucogingival Junction Determination

Abstract: Intra- and inter-examiner reproducibility has been shown to be substantially consistent when different methods for MGJ determination are used to measure the apico-coronal dimension of the gingiva. The level of reproducibility does not seem to be affected whether or not the mucogingival complex has been surgically altered by a gingival augmentation procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 16 publications
(16 reference statements)
2
44
0
2
Order By: Relevance
“…These results are consistent with the research of Guglielmone et al, 24 while Bernimoulin et al 25 reported that performing the functional method gives a maximum width of keratinized gingiva. In addition, the visual method after staining the gingival tissue leads to the smallest disagreements in the values of the attached gingiva width compared to other methods of determining the width of the attached gingiva.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with the research of Guglielmone et al, 24 while Bernimoulin et al 25 reported that performing the functional method gives a maximum width of keratinized gingiva. In addition, the visual method after staining the gingival tissue leads to the smallest disagreements in the values of the attached gingiva width compared to other methods of determining the width of the attached gingiva.…”
Section: Discussionsupporting
confidence: 92%
“…Ovi rezultati su u skladu sa istraživanjem Guglielmoni et al 24 , dok Bernimoulin et al 25 prijavljuje da izvođenje funkcionalne metode daje najveću širinu keratinizirane gingive. Osim toga, vizuelna metoda, nakon bojenja gingivalnog tkiva, dovodi do najmanjeg neslaganja vrednosti širine pripojne gingive u poređenju sa drugim metodama određivanja širine pripojne gingive.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Gingival width was measured midbuccally and, at mandibular teeth, midlingually over the root prominence with the periodontal probe to the nearest millimetre. The mucogingival border was identified by inspecting mucosal surface characteristics as colour and stippling and, if in doubt, functionally by applying a periodontal probe to the alveolar mucosa parallel to the border thereby demarcating the zone of the attached gingiva [7].…”
Section: Methodsmentioning
confidence: 99%